Penang international airport relocation: Should or should not? - Ng, Shin Xian; Wan Mohd Nordin, Wan Shuhadah; Md Said, Mohamad Hafiz; Sabar, Rohafiz (2012)
The aim of this research is to study the factors and issues and identify the possibility of Penang International Airport whether need to relocate.The study was conducted by distributing questionnaires to undergraduate students who are mostly from University Utara Malaysia who had experienced the flight from or to Penang International Airport.By using descriptive and case studies analysis, the relationships between the independent and dependent variables were identified.The research’s goal is designed to make clarification about the relocation of Penang airport to the new location and the study of relocation of Penang airport issue can be a learning paradigm for the future generations to enhance their knowledge and management skills as well.